Heat and Mass Transfer of an MHD Casson Fluid with Variable Properties and Non-Linear Thermal Radiation Over an Elastic Sheet - Kasali, Kazeem Babawale; Gbadamosi, Babatunde; Familua, Adefunke Bosede; Tairu, Muhammed Lolade (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2024)
The study of heat and mass transfer is germane due to its numerous scientific and technological relevance. This work investigates heat and mass transmission of an MHD Casson fluid flow over an elastic sheet under the influence of nonlinear thermal radiation, chemical reaction, and varying thermal conductivity and diffusion coefficient. The flow models that describe the fluid behaviour are reduced to a non-dimensional form with suitable similarity variables. The resulting dimensionless models are admissible to the shooting method technique to obtain the model parametric analysis. The responses of different emerging parameters are shown on the fluid profiles through graphs. It is observed that the augmentation of magnetic field parameters boosts the boundary layer thickness thereby hindering the fluid's velocity while the direct relationship is recorded with the fluid's temperature. Findings also reveal that thermal radiation and temperature-dependent thermal conductivity parameters augment the temperature of the fluid.